VISI PROFETIK HAJI: STRATEGI KEBUDAYAAN DALAM TRANSFORMASI SOSIAL - Suwito Suwito (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2013)
This article describe and analyze the prophetic vision of hajj in AliSyari’ati perspective. The analysis applies social approach as stated byKuntowijoyo as prophetic social science. There are three aims on propheticsocial, humanism, liberation and transcendence. This article showsthat hajj does not only make people closer to the God but also teach themto be more sensitive to the environment. There are three essential meanings,humanism, liberalism and transcendence.